A splicing variant of TERT identified by GWAS interacts with menopausal estrogen therapy in risk of ovarian cancer. Issue 12 (16th September 2016) - Lee, Alice W.; Bomkamp, Ashley; Bandera, Elisa V.; Jensen, Allan; Ramus, Susan J.; Goodman, Marc T.; Rossing, Mary Anne; Modugno, Francesmary; Moysich, Kirsten B.; Chang‐Claude, Jenny; Rudolph, Anja; Gentry‐Maharaj, Aleksandra; et al.
Abstract : Menopausal estrogen‐alone therapy (ET) is a well‐established risk factor for serous and endometrioid ovarian cancer. Genetics also plays a role in ovarian cancer, which is partly attributable to 18 confirmed ovarian cancer susceptibility loci identified by genome‐wide association studies. The interplay among these loci, ET use and ovarian cancer risk has yet to be evaluated. We analyzed data from 1, 414 serous cases, 337 endometrioid cases and 4, 051 controls across 10 case–control studies participating in the Ovarian Cancer Association Consortium (OCAC). Conditional logistic regression was used to determine the association between the confirmed susceptibility variants and risk of serous and endometrioid ovarian cancer among ET users and non‐users separately and to test for statistical interaction. A splicing variant in TERT, rs10069690, showed a statistically significant interaction with ET use for risk of serous ovarian cancer ( p int  = 0.013). ET users carrying the T allele had a 51% increased risk of disease (OR = 1.51, 95% CI 1.19–1.91), which was stronger for long‐term ET users of 10+ years (OR = 1.85, 95% CI 1.28–2.66, p int  = 0.034). Non‐users showed essentially no association (OR = 1.08, 95% CI 0.96–1.21). Two additional genomic regions harboring rs7207826 (C allele) and rs56318008 (T allele) also had significant interactions with ET use for the endometrioid histotype ( p int  = 0.021 and p int  = 0.037, respectively). Hence, three confirmed susceptibility variants were identified whose associations with ovarian cancer risk are modified by ET exposure; follow‐up is warranted given that these interactions are not adjusted for multiple comparisons. These findings, if validated, may elucidate the mechanism of action of these loci. Abstract : What's new? Menopausal estrogen‐alone therapy (ET) is a well‐established risk factor for serous and endometrioid ovarian cancer. Genetics also plays a role in ovarian cancer, with 18 ovarian cancer susceptibility loci already confirmed. The interplay among these loci, ET use and ovarian cancer risk has yet to be evaluated. This study identifies three confirmed susceptibility variants whose associations with ovarian cancer risk are modified by ET exposure. Of particular interest is the interaction with rs10069690, a functional variant located in TERT . The findings, if validated, may elucidate the mechanism of action of these loci and be critical for future risk prediction modeling.